WordNet-based Computation of Semantic Similarity Between Two Vietnamese Nouns - Phan , Trang Thi My; Duong , An Thi; Tran , Phuong Thi Minh (Technium Social Sciences Journal, 2023)
Abstract. This study aimed to measure the semantic distance between Vietnamese nouns to determine their similarities and differences in terms of semantics. The study utilized a dataset of 1000 randomly selected noun pairs from the Vietnamese WordNet and applied different semantic distance measurement formulas, such as Path-length, Leacock & Chodorow, Wu & Palmer, Resnik, Lin, and Jiang-Conrath measures. The results showed that the Resnik measure is suitable for evaluating noun similarity among primitive concepts of the same class and for measuring proximity between two classes of primitive concepts. On the other hand, the Leacock & Chodorow measure is appropriate for measuring the semantic distance between nouns belonging to two distant classes of primitive concepts. The methods used in this study have various potential applications in different fields of linguistics, such as determining synonyms, identifying semantically similar words, defining lexical-semantic fields, and detecting plagiarism.